Transmissão de força miofascial do músculo grande dorsal para o glúteo máximo contralateral: uma investigação in vivo - Viviane Otoni Carvalhais (2012)
Introduction: Studies have demonstrated that the tension produced by a muscle can be transferred to anatomically distant structures through the connective tissue network of the human body. The extensive connection of latissimus dorsi (LD) and gluteus maximus (GM) muscles to thoracolumbar fascia (TLF) and the oblique orientation of their fibers suggest the occurrence of myofascial force transmission between these muscles. However, studies about force transference from LD or GM to TLF were performed in cadavers. This fact limits the generalization of results for in vivo contexts. One way to show myofascial force transmission from LD to GM in vivo could be the investigation if the tension produced in LD is able to modify the passive behavior of the contralateral hip, such as resting position (RP) and passive stiffness of this joint. Objective: To investigate whether passive or active tensioning of LD are able to change the RP and the passive stiffness of the contralateral hip in healthy subjects. Materials and method: A quasi-experimental study was conducted with 37 volunteers of both sexes, with mean age of 24.92 ± 3.21 years. The participants underwent assessment of hip passive resistance torque during medial rotation motion using an isokinetic dynamometer. This measure was carried out in three test conditions: 1) Control; 2) LD passive tensioning and 3) LD active tensioning. During the measurement of hip passive resistance torque, electromyography was used to monitor the activity of hip muscles and LD in all test conditions. Hip RP and passive stiffness were the dependent variables obtained from the test performed on isokinetic dynamometer. Repeated measures analyses of variance were performed to investigate whether LD passive or active tensioning were able to modify the passive behavior of the contralateral hip. Significance level was set at 0.05 for all analyses. Results: LD passive tensioning shifted the hip RP toward lateral rotation (p = 0.009). This result demonstrated that the additional tension received by GM after LD stretching was enough to make the GM to resist hip medial rotation with higher torque at each joint position. However, LD stretching did not change significantly hip passive stiffness (p > 0.05). LD active tensioning also shifted the RP toward lateral rotation (p < 0.001). Furthermore, this condition resulted in increase of passive stiffness (p 0.004), i.e. LD contraction increased the rate of change in the resistance torque to hip angular displacement. Conclusion: The manipulation of LD tension modified the passive behavior of the contralateral hip, which supports the existence of myofascial force transmission from LD to GM via TLF in vivo. The results of the present study suggest that part of the tension produced during stretching or contraction of muscles is capable to propagate along the fascial connective tissue and affect the mechanical behavior of anatomically distant structures